PTV Vissim Calibration and Validation of Median Opening U-Turn - Karimi, Muh Bahrul Ulum Al; Haryadi, Bambang; Setiadji, Bagus Hario; Mahfuda, Anno (Rekayasa Sipil, 2025)
Traffic conditions at a median opening are more complex than signalized or unsignalized intersections. Driving behaviors and the driver's ability to maneuver a U-turn can affect median opening performance. Using software such as PTV Vissim, simulations can be carried out to help analyze traffic conditions and make necessary decisions. This study aims to simulate the median opening u-turn using PTV Vissim to resemble actual traffic conditions and validate it statistically. The calibration involves adjusting traffic volume, headway distribution, speed distribution, driving behaviors, conflict area, and critical gap. One of the important parameters in an unsignalized intersection, especially for U-turn movements at median openings, is the necessary gap. Most simulations still focus on driving behavior parameters, while the critical gap should be used as a calibration parameter to determine safe distances. Additionally, headway distribution predicts the arrival of vehicles that will pass through the median opening. This study adds calibration to the headway distribution parameter and critical gap parameter. The validation MAPE and GEH results for the calibrated simulation are good and acceptable. Meanwhile, the uncalibrated (default) simulation shows poor and unacceptable values. This evidence indicates that calibration is essential in the PTV Vissim simulation. Factors that affect the simulation result are inconsistent drivers, aggressive driver behavior, and inability to comply with priority rules. Driving patterns in mixed and heterogeneous traffic conditions create opportunities and spaces for making U-turns. Simulating this factor is challenging, so a more careful calibration is needed.